Characterization of Aeroelastic Behavior in a High Aspect Ratio Wing Using Computational and Wind Tunnel Experiments - Westin, Michelle F.; Balthazar, Jose M. [UNESP]; da Silva, Roberto G. A.; Ribeiro, Mauricio A.; Tusset, Angelo M. (MDPI, 2023)
The objective of this article is to characterize an aeroelastic system in terms of its dynamical behavior, which could be either chaotic or periodic before, during, and after achieving the flutter velocity. The aeroelastic system shown here is a wing with a high aspect ratio, which leads to a very flexible behavior subjected to unsteady flow. This paper compares the computational and experimental dynamical behavior of an aeroelastic system at the flutter velocity for the different dynamic stall models proposed. To understand the nonlinear behavior of this system, the traditional attractor reconstruction and Lyapunov exponent calculation are compared with the 0–1 test. In addition to this comparison, two dynamic stall semi-empirical models are applied directly to the time history. All these comparisons show that the computational and wind tunnel experiments are in good agreement, and the dynamic behavior usually gives close results for the 0–1 test and Lyapunov exponent. It is concluded that the system presents chaotic behavior when no dynamic stall correction is applied or when Gangwani’s correction is applied. However, Boeing–Vertol’s correction postpones the chaotic behavior, meaning that the chaotic behavior is only observed for velocities above the flutter.
Keywords: chaos; flexible wing; high aspect ratio; nonlinear aeroelasticity